Persepektif Gender Dalam Novel Mataraisa Karya Abidah El Khalieqi:Pendekatan Feminisme Dan Implementasinya Pada Pembelajaran Sastra Di SMP - PURWANINGSIH, IDHA, Prof. Dr. Ali Imron Al Ma'ruf, M.Hum, Dr Nafron Hasyim (2016)
This study aimed to describe 1) the structure 2) the nature of gender equality in the work Mataraisa novel Abidah El Khalieqy, and 3) the implementation of novel research results Mataraisa by Abidah El Khalieqy work in teaching literature in junior high school. The data in this study in the form of words, sentences, phrases, and the discourse that contain elements of gender issues in the novel Mataraisa. Mechanical footage used is purposive sampling while collecting data using content analysis. Test the validity of the data that is applied is triangulation. Data were analyzed using reading techniques semiotic models consisting of heuristic and hermeneutic reading. The results showed that 1) Mataraisa novel structure that is based on the theory of fiction Robert Stanton theme of women in the struggle for gender equality with men. The fact the novel is divided into three, namely: character and characterization, setting, and plot. 2) As a form of gender equality, namely: (a) women as equals to men, (b) the rights and obligations similarities between men with women, and (c) against violence against women. 3) The results are implemented in the learning scenarios with KD 14.2 Responding to an interesting quote from juvenile novel (original or translation), which is scheduled in two meetings. The first meeting, focused on the delivery of content on the novel, novel intrinsic elements, aspects of gender inequality and ordinances argue with courtesy, good, and true as well as the provision of duty of teachers. The second meeting was followed by a presentation and discussion of the results of the tasks that have been worked on the student.